Numerical simulation and experimental investigation of laser joining Ti6Al4V alloy and CFRTP with embedded Ti6Al4V alloy. (December 2022) - Xu, Ying; Bu, Hengchang; Wang, Feiyun; Ma, Wanping; Zhan, Xiaohong
Highlights: A new laser joining of CFRTP with embedded Ti6Al4V alloy and Ti6Al4V alloy is investigated. The finite element model for laser joining of Ti6Al4V alloy and CFRTP with embedded Ti6Al4V alloy is established. The temperature fieldfor the laser joining of CFRTP with embedded Ti6Al4V alloy and Ti6Al4V alloy are analyzed. The tensile failure load exceeds 10195.6 N and the fatigue load at one million cycles is 1722.3 N. Abstract: Laser joining technology shows a great application prospect in the connection of Carbon Fiber Reinforced Thermoplastic Composite (CFRTP) and titanium alloy with the advantages of high production flexibility and strong heat input controllability. In this paper, a laser joining of the Ti6Al4V alloy and the CFRTP with embedded Ti6Al4V alloy is proposed to enhance the mechanical properties of laser joining CFRTP and titanium alloy. The CFRTP with embedded Ti6Al4V alloy is prepared by hot-pressing. Numerical simulations of laser joining the Ti6Al4V alloy and the CFRTP with embedded Ti6Al4V alloy are performed by applying the finite element method. To better understand the process parameters, the joining process under different laser powers and scanning speeds are simulated, and the temperature field and the shape of molten pool are calculated. In addition, the shape of molten pool calculated using the simulation model exhibits good agreement with experimental results to substantiate the established model. The microstructure characteristics and energy dispersive spectroscopy results are analyzed. The failure load, fatigue life, and failure mode for laser joining CFRTP/Ti6Al4V alloy are studied. The results indicate that the tensile failure load of the joint exceeds 10195.6 N, obtained by using the optimal process parameters based on simulation. The tensile fracture occurs in CFRTP base material. Moreover, the specimen ruptures at the overlap region of Ti6Al4V alloy under fatigue cyclic loading and the fatigue failure mode is edge through crack growth failure.